The Application of High-Throughput Technologies for the Study of Microbiome and Cancer - Wei, Lu Qi; Cheong, Io Hong; Yang, Guang Huan; Li, Xiao Guang; Kozlakidis, Zisis; Ding, Lei; Liu, Ning Ning; Wang, Hui (Frontiers in Genetics, 2021)
Human gut microbiome research has been developing at a considerable pace over the last decades, driven by a rapid technological advancement. The emergence of high-throughput technologies, such as genomics, transcriptomics and others have afforded the generation of large volumes of data, and in relation to specific pathologies such as different cancer types. The current review identifies high-throughput technologies as they have been implemented in the study of microbiome and cancer. Four main thematic areas have emerged; the characterization of microbial diversity, the microbial functional analyses, biomarker prediction and lastly, potential therapeutic applications. The majority of studies identified focus on the microbiome diversity characterization which is reaching technological maturity, while the remaining three thematic areas could be described as emerging.